Application of a remotely bonded fiber-optic Bragg grating sensor to acoustic emission testing for a carbon-carbon composite at a temperature of 1000 °C. (15th November 2022) - Yu, Fengming; Li, Zixuan; Okabe, Yoji
Highlights: A heat-resistant fiber Bragg grating (FBG) sensor was used for in-situ acoustic emission (AE) testing at 1000 °C. Real damage-induced AE signals in a heat-resistant composite material was received with high sensitivity and high stability at different temperatures. Machine learning-based clustering analysis and waveform analysis of the acquired AE signals were conducted for damage type identification in the composite. The AE testing was used to study the failure process of the heat-resistant composite after being oxidized. Abstract: This research established an acoustic emission (AE) testing method applicable at high temperatures using a fiber Bragg grating (FBG) sensor. The method was employed to inspect the process of flexural failure of a heat-resistant carbon–carbon (CC) composite material during a three-point bending test conducted at a temperature as high as 1000 °C. This paper reported the AE testing results. Also, the AE signals with different waveform features were classified by a clustering analysis based on machine learning. Those different AE signal clusters were further associated with different damages, such as matrix crack, inter-ply delamination, and breakage of the fiber bundles. The relation between the damage mechanism and the material failure was then investigated based on the classified AE testing results. The investigation clarified that the progressive behavior of those damages depended on the extent of the material oxidation at elevated temperatures. The analysis agreed with the microscopic cross-section observation. Hence, this article demonstrated that the FBG-based AE testing method was capable of reliable in-situ damage diagnosis under high-temperature environments.